Thulium-aluminum co-doped calcium fluoride near-middle infrared band laser crystal and preparation method and application thereof
Through the preparation of thulina aluminum co-doped calcium fluoride laser crystals, the local coordination structure and the addition of Al3+ ions are regulated, the existing near-mid-infrared lasers are solved, and efficient 1.5μm and 2μm laser output is achieved, and the beam quality is improved.
Patent Information
- Application Number
- CN202510526277.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-25
- Publication Date
- 2025-08-01
- Estimated Expiration
- 2045-04-25
AI Technical Summary
The existing near-mid infrared lasers have problems with high cost and poor beam quality, especially the laser output efficiency of rare earth ion-doped solid or fiber lasers in the 1.5μm and 2μm bands, and are prone to self-termination.
A near-mid-infrared infrared band laser crystal is used to regulate the local coordination structure inside the crystal and dopant Al3+ ions to form a disorderly distributed mixed fluoride crystal, which enhances the splitting between energy levels, achieves new fluorescence peaks, and improves laser output efficiency.
The 1.5μm and 2μm laser output with high output power is achieved, which improves the beam quality and efficiency of the laser, overcomes the self-termination phenomenon, and has better application potential.
Smart Images

Figure CN120400997A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of laser materials, and relates to a near-infrared laser crystal and a preparation method thereof, in particular to a thulium-aluminum co-doped calcium fluoride near-infrared laser crystal, a preparation method thereof and an application thereof. Background Art
[0002] With the informatization process of the times, people have an increasing demand for lasers in special wavelength bands. This situation has promoted the research focus in related fields to shift towards high-performance lasers in new wavelength bands. Among them, near-infrared lasers have received extensive attention due to their wide application fields in life. The infrared spectrum is usually divided into three regions: the near-infrared region (0.75 - 2.5 μm), the mid-infrared region (2.5 - 25 μm), and the far-infrared region (25 - 300 μm). Due to differences in application requirements, different fields have different definitions for the range of infrared wavelengths. In the laser field, the wavelength range of near-infrared is generally defined as 1 - 5 μm. Near-infrared lasers have important applications in medical treatment, military, communication detection, etc.
[0003] Currently, there are mainly three methods to achieve near-infrared lasers:
[0004] 1) Activator ion-doped lasers, by utilizing specific near-infrared transitions in activator ions, prepare laser materials such as ion-doped crystals, glasses, ceramics, and optical fibers. Such lasers have become an important choice in fields such as medical treatment and environmental monitoring due to their small size, high stability, and excellent beam quality.
[0005] 2) Optical parametric technology, using nonlinear technologies such as optical parametric oscillation, optical parametric amplification, difference frequency, and sum frequency frequency conversion technologies, through nonlinear materials, tune the mature short-wavelength band lasers to obtain mid-infrared lasers. For example, a spatial optical structure mid-infrared supercontinuum light source provided by patent CN119395896A uses a grating pair to compress pulses and combines fluoride optical fibers to achieve the broadening of the supercontinuum spectrum; this technology expands the mid-infrared laser wavelength range through nonlinear effects (such as supercontinuum generation) and is applicable to fields such as optical communication and environmental monitoring.
[0006] 3) A semiconductor laser forms a population inversion between the conduction band and the valence band through an excitation method. When electrons at the bottom of the conduction band recombine with holes at the top of the valence band, stimulated emission occurs. Commonly used semiconductor lasers include InGaAsSb, AlGaAsS, etc. For example, Patent CN119354919A provides a method for detecting ethane and methane dual gases based on a mid-infrared laser. This invention uses the DAC pin of a single-chip microcomputer to output a sawtooth scanning signal superimposed with a sine wave modulation. By adjusting the amplitude of the sawtooth scanning signal, the wavelength of the laser emission is controlled between 3344.4 nm and 3345.8 nm, covering the absorption peak positions of ethane and methane simultaneously, achieving the simultaneous detection of the ethane and methane dual components. Patent CN118905417B provides a data processing system for a black phosphorus-based mid-infrared band laser, which relates to the technical field of mid-infrared band lasers. By integrating emission, regulation, detection, processing, feedback, and interaction modules, the manipulation and intelligent analysis of mid-infrared laser pulses are realized.
[0007] Although the optical parametric technology can utilize existing lasers, it has a high cost and is not convenient for application; semiconductor lasers also have problems such as low power and poor beam quality; while doped active ion solid or fiber lasers, especially those doped with rare earth ions, not only have a small volume and are convenient to use, but also operate stably, have a high output beam quality, and high efficiency, and are increasingly attracting the attention of researchers in modern society. Summary of the Invention
[0008] Based on the defects existing in the above-mentioned prior art, the object of the present invention is to provide a thulium-aluminum co-doped calcium fluoride near mid-infrared band laser crystal, its preparation method and application, and the laser crystal can generate new fluorescence peaks after co-doping ions.
[0009] The object of the present invention can be achieved through the following technical solutions:
[0010] One of the technical solutions of the present invention provides a thulium-aluminum co-doped calcium fluoride near mid-infrared band laser crystal, and its chemical composition is expressed as Tm x Al y Ca 1-x-y F2, where 0.001 ≤ x ≤ 0.01 and 0.05 ≤ y ≤ 0.5; Tm represents thulium, Al represents aluminum, Ca represents calcium, and F represents fluorine.
[0011] Preferably, x = 0.005 and 0.1 ≤ y ≤ 0.5, that is, the chemical composition of the preferably thulium-aluminum co-doped calcium fluoride near mid-infrared band laser crystal is expressed as Tm 0.005 Al y Ca 0.995-y F2;
[0012] Further, when x = 0.005 and 0.1 ≤ y ≤ 0.5, the space group of the crystal is Fm-3m, belonging to the cubic crystal system and having high symmetry. Among them, "F" represents a face-centered cubic lattice, meaning that there are atomic distributions at the eight vertices and the centers of the six faces of the unit cell; "m-3m" indicates that the crystal has multiple symmetry elements, including mirror planes (m), three-fold rotation axes (-3), and inversion centers, etc. The combination of these symmetry elements determines the positional relationship of atoms in the crystal and the macroscopic symmetry of the crystal. Specifically, the crystal of this space group has specific symmetry operations along the crystal axis direction, the face diagonal direction, and the body diagonal direction, making the crystal exhibit similar structures and properties in different directions.
[0013] The second technical solution of the present invention provides a preparation method of a thulium-aluminum co-doped calcium fluoride near-infrared laser crystal, comprising the following steps:
[0014] 1) Using TmF3, AlF3, and CaF2 as raw materials, calculate the required mass of each raw material according to the chemical formula Tm x Al y Ca 1-x-y F2 and weigh; fully grind the weighed raw materials, mix them evenly, and then put them into a container; add a deoxidizer, cover the container lid; obtain a mixed material;
[0015] 2) Place the mixed material in step 1) in a thermal field for vacuum pumping. After the vacuum degree reaches below 8 Pa, fill it with a protective gas until zero positive bias; then perform a process of heating - holding - slow cooling - cooling to obtain a crystal, which is a thulium-aluminum co-doped calcium fluoride near-infrared laser crystal.
[0016] Further, the states of the TmF3, AlF3, and CaF2 raw materials in step 1) are single crystal particles or powders, and the purity of the single crystal particles or powders of TmF3, AlF3, and CaF2 is 5N. The 5N purity has less impurity content compared to the raw materials of chemical analytical purity and 4N purity, which can avoid problems such as difficulty in obtaining crystals and poor crystal quality caused by the reaction of impurities with the container and raw materials during the growth process.
[0017] The grinding time in step 1) is 40 - 60 min, preferably 40 min;
[0018] The deoxidizer in step 1) is PbF2, and its function is to prevent the calcium fluoride raw material from being oxidized; the addition amount of the deoxidizer is 1 - 3% of the total mass of TmF3, AlF3, and CaF2, preferably 1%;
[0019] The container in step 1) is preferably a porous graphite crucible, and its corresponding container lid is a graphite lid;
[0020] Furthermore, the vacuum pumping process described in step 2) includes rough vacuum pumping by a mechanical pump and fine vacuum pumping by a molecular pump;
[0021] The protective gas described in step 2) is preferably at least one of argon or fluorine-containing gas; specifically, the fluorine-containing gas is at least one of CF4 or HF.
[0022] The temperature increase in step 2) is as follows: the temperature is increased to 1400 - 1700 °C at a rate of 200 - 300 °C / h; the heat preservation time is 10 - 15 hours to ensure complete melting of materials and removal of impurities; the slow temperature decrease is as follows: the temperature is slowly decreased to 1000 - 1200 °C at a rate of 1 - 3 °C / h for crystal growth; the cooling is as follows: after the slow temperature decrease for crystal growth is completed, the temperature is decreased to room temperature at a rate of 50 - 60 °C / h.
[0023] Currently, the rare earth ions that can obtain laser output in the 1.5 - 3.5 μm near - mid - infrared region mainly include thulium (Tm), holmium (Ho), erbium (Er), dysprosium (Dy), etc. Compared with other rare earth ions, the Tm 3+ ion has absorption energy in the 1.5 μm and 2 μm bands that can match the common pump sources, and the relatively wide gain bandwidth enables the laser to have tunable capabilities. The Tm 3+ ion is formed by the 4f 13 6s 2 electron layer of the Tm atom (outer electron distribution) losing one electron and the 6s electron layer losing two electrons. The main absorption band of the Tm 3+ ion corresponds to 3 H6→ 3 H4 transition, with a wavelength near 800 nm, which is very consistent with the emission wavelength of the GaAsAl laser diode. Therefore, a high - power GaAsAl laser can be used as a pump source for the Tm 3+ ion - doped laser medium. The main luminescence of the Tm 3+ ion in the near - mid - infrared band is as follows: the transitions corresponding to 1.5 μm, 2 μm, and 2.3 μm are 3 H4→ 3 F4, 3 F4→ 3 H6, 3 H4→ 3 H5.
[0024] In the Tm 3+ ion, 3 the energy level spacing between H4 and 3 F4 is relatively close to the energy level spacing between 3 F4 and 3 H6. Therefore, cross - relaxation phenomenon (Cross Relaxation, CR) is very likely to occur. The pump light will pump the ground state energy level 3The number of particles of H6 is pumped to 3 the H4 energy level through the cross-relaxation process 3 H4(Tm 3+ )+ 3 H6(Tm 3+ )→ 3 F4(Tm 3+ )+ 3 F4(Tm 3+ ). As a result, the number of particles at the F4 energy level doubles, and then through 3 the F4→ 3 H6 emission transition, 2-μm laser is generated. Through the cross-relaxation process, the theoretical quantum efficiency of the 2-μm laser can reach 200%, that is, one pump photon can generate two 2-μm laser photons. Therefore, Tm 3+ ion-doped laser media have achieved high output power and high slope efficiency lasers in the 2-μm band and have been put into practical use. In 2007, researchers obtained a continuous laser output of 1.9 μm with an output power of 64 W and a slope efficiency of 68% in Ge fiber doped with Tm 3+ ions. By 2010, Tm 3+ ion-doped fiber lasers had achieved kilowatt-level output power.
[0025] Although the cross-relaxation phenomenon is very beneficial to the 2-μm laser output of Tm 3+ ions, it has the opposite effect on the luminescence at 1.5 μm and 2.3 μm. Especially for 1.5 μm, the lifetime of the lower energy level 3 F4 is one order of magnitude higher than that of the upper energy level 3 H4, which will lead to the self-termination phenomenon of the 1.5-μm laser. To achieve the laser output at 1.5 μm and 2.3 μm, an important way is to suppress the cross-relaxation phenomenon and achieve population inversion. By regulating the local coordination inside the crystal, the near-infrared luminescence of Tm 3+ ions can be regulated.
[0026] The disordered hybrid Tm 0.005 Al 0.1 Ca 0.895 F2 crystal still belongs to the cubic crystal system. In addition to having a lower phonon energy, it also regulates the local coordination structure of Tm 3+ ions at the atomic, molecular and group scales. When introducing the doping ion Al 3+ ions into the Tm:CaF2 crystal, both Al 3+ and Tm 3+ will replace the Ca 2+ lattice sites. On the one hand, the incorporation of Al 3+ ions can improve Tm 3+ ions, on the other hand, it can also... 3+The cluster state of ions to achieve efficient laser output. On the other hand, Al 3+ The incorporation of ions to form a mixed fluoride crystal with a disordered distribution of (Ca,Al)F2 in the form of compound components, creating a truly effective "disorder" of the active ions, enhancing the splitting between energy levels, and thus splitting new fluorescence peaks at 1.5 μm and 2 μm.
[0027] Based on the above theory, the present invention has developed a laser material that can generate new laser wavelengths compared to existing fluorides and is more promising for achieving laser output at 1.5 μm and 2 μm.
[0028] The third technical solution of the present invention provides an application of a thulium-aluminum co-doped calcium fluoride near-infrared laser crystal. The laser crystal is used as a gain medium to construct a high-power near-infrared laser.
[0029] Compared with the prior art, the present application has at least the following improvements and beneficial effects:
[0030] Taking the specific embodiment of the present invention as an example, the present invention selects (Ca,Al)F2 as the laser crystal matrix material, and dopes Tm 3+ ions into the (Ca,Al)F2 lattice through the temperature gradient method. The relatively low phonon energy of (Ca,Al)F2 is beneficial to reducing non-radiative transitions caused by multi-phonon relaxation, which greatly improves the output efficiency of near-infrared lasers. In addition, the disordered mixed crystal also regulates the local coordination structure of Tm 3+ ions at the atomic, molecular, and group scales, forming a truly effective "disorder" of the active ions, enhancing the splitting between energy levels, and thus splitting new fluorescence peaks at 1.5 μm and 2 μm. Based on the above analysis, Tm 0.005 Al 0.5 Ca 0.915 F2 crystal can achieve higher output power than existing fluorides and has good application potential in aspects such as laser materials for laser output at 1.5 μm and 2 μm. Description of the Drawings
[0031] Figure 1 The room-temperature absorption coefficient spectrum of the thulium-aluminum co-doped calcium fluoride near-infrared laser crystal Tm 0.005 Al 0.5 Ca 0.495 F2 prepared in Example 1;
[0032] Figure 2 The room-temperature fluorescence spectra of the thulium-aluminum co-doped calcium fluoride near-infrared laser crystals prepared in Examples 1 to 3 at (a) 1.5 μm and (b) 2 μm;
[0033] Figure 3Tm,Al co-doped calcium fluoride near-infrared laser crystal Tm 0.005 Al 0.5 Ca 0.495 F2 under 808 nm light excitation, (a) 3 H4 and (b) 3 Fluorescence lifetime spectra corresponding to the F4 energy level;
[0034] Figure 4 Tm,Al co-doped calcium fluoride near-infrared laser crystal Tm 0.005 Al 0.1 Ca 0.895 F2 under 808 nm light excitation, (a) 3 H4 and (b) 3 Fluorescence lifetime spectra corresponding to the F4 energy level;
[0035] Figure 5 Tm,Al co-doped calcium fluoride near-infrared laser crystal Tm 0.005 Al 0.3 Ca 0.695 F2 under 808 nm light excitation, (a) 3 H4 and (b) 3 Fluorescence lifetime spectra corresponding to the F4 energy level.
[0036] Figure 6 Tm-doped calcium fluoride near-infrared laser crystal Tm prepared in Comparative Example 1 0.005 Ca 0.995 Room temperature fluorescence spectra of F2 at (a) 1.5 μm and (b) 2 μm;
[0037] Figure 7 Tm-doped calcium fluoride near-infrared laser crystal Tm prepared in Comparative Example 1 0.005 Ca 0.995 F2 under 808 nm light excitation, (a) 3 H4 and (b) 3 Fluorescence lifetime spectra corresponding to the F4 energy level; Detailed implementation manners
[0038] To enable those skilled in the art to better understand the technical solutions of the present invention, the present invention will be described in detail below with reference to specific embodiments. It should be noted that the following embodiments will help those skilled in the art to further understand the present invention, but do not limit the present invention in any form. It should be pointed out that for those of ordinary skill in the art, without departing from the concept of the present invention, several modifications and improvements can be made. These all belong to the protection scope of the present invention.
[0039] There are no particular restrictions on the sources of all raw materials of the present invention, and they can be purchased on the market or prepared by conventional methods well-known to those skilled in the art.
[0040] Example 1:
[0041] A thulium-aluminum co-doped calcium fluoride near-infrared laser crystal Tm 0.005 Al 0.5 Ca 0.495 F2, and its preparation method includes the following steps:
[0042] 1) Using TmF3, AlF3, and CaF2 single crystal particles as raw materials, weighing according to the chemical formula Tm 0.005 Al 0.5 Ca 0.495 F2, totaling 25 g, grinding thoroughly for 60.0 min and mixing evenly, and then loading into a porous graphite crucible; adding 1.25 g of PbF2 as a deoxidizer to the above porous graphite crucible and covering it with a circular graphite lid;
[0043] 2) Placing the porous graphite crucible in step 1) in a roasting furnace, evacuating to make the vacuum degree in the furnace reach below 8 Pa, then filling the furnace with argon as a protective atmosphere to zero positive bias; then starting the heating program, continuing to heat at a rate of 200.0 °C / h to 1500 °C, and holding for 12 hours to ensure complete melting of the materials and removal of impurities; then slowly cooling to 1100 °C at a rate of 2.0 °C / h for crystal growth. After the growth is completed, cooling to room temperature at a rate of 50.0 °C / h, and taking out to obtain a Tm 0.005 Al 0.5 Ca 0.495 F2 crystal, that is, the thulium-aluminum co-doped calcium fluoride near-infrared laser crystal.
[0044] Characterize the Tm 0.005 Al 0.5 Ca 0.495 F2 crystal prepared in this example, including: determination of the room temperature absorption coefficient, determination of the room temperature fluorescence spectrum, and determination of the fluorescence lifetime. The above experiments are carried out in a UV-Vis-NIR spectroscopy system (Cary 5000 UV / VIS / NIR) and an Edinburgh FLS1000 fluorescence spectrometer respectively, and the operation methods are all common knowledge to those skilled in the art and can be carried out according to the instrument instructions. The results are as follows:
[0045] As Figure 1 shown is the room temperature absorption coefficient spectrum of the prepared Tm 0.005 Al 0.5 Ca 0.495 F2 sample. It can be seen that it is in good agreement with the emission wavelength of the GaAsAl laser diode.
[0046] like Figure 2 Shown is the Tm of the preparation 0.005 Al 0.5 Ca 0.495 From the room temperature fluorescence spectra of F2 sample at 1.5μm and 2μm, we can see that Tm 3+ New fluorescence peaks are split at around 1420 nm and 2050 nm. Combining the results provided in Example 2 and Example 3, it can be found that the emission intensity increases with the increase of Al ion concentration.
[0047] like Figure 3 Shown is the Tm of the preparation 0.005 Al 0.5 Ca 0.495 The fluorescence lifetime spectrum of the F2 sample under 808nm light excitation, corresponding to the emission peaks of 1.5μm (corresponding to H, the same below) and 2μm (corresponding to F, the same below), shows that the sample 3 The lifetime of the H4 level is 1.55ms. 3 The lifetime of the F4 level is 12.3ms.
[0048] Example 2:
[0049] A thulium aluminum co-doped calcium fluoride near-mid-infrared laser crystal Tm 0.005 Al 0.1 Ca 0.895 F2, its preparation method is the same as that of Example 1.
[0050] like Figure 2 Shown is the Tm of the preparation 0.005 Al 0.1 Ca 0.895 From the room temperature fluorescence spectra of F2 sample at 1.5μm and 2μm, we can see that Tm 3+ New fluorescence peaks are split at around 1420 nm and 2050 nm. Combining the results provided in Example 1 and Example 3, it can be found that the emission intensity increases with the increase of Al ion concentration.
[0051] like Figure 4 Shown is the Tm of the preparation 0.005 Al 0.1 Ca 0.895 The fluorescence lifetime spectrum of the F2 sample under 808nm light excitation corresponds to the 1.5μm and 2.3μm emission peaks. It can be seen that the sample 3 The lifetime of the H4 level is 1.05ms. 3 The lifetime of the F4 level is 16.9ms.
[0052] Example 3:
[0053] A thulium aluminum co-doped calcium fluoride near-mid-infrared laser crystal Tm0.005 Al 0.3 Ca 0.695 F2, the preparation method thereof is the same as that of Example 1.
[0054] As Figure 2 shown is the room temperature fluorescence spectra of the prepared Tm 0.005 Al 0.1 Ca 0.895 F2 samples at 1.5 μm and 2 μm. It can be seen that Tm 3+ splits new fluorescence peaks at around 1420 nm and 2050 nm, and combining the results provided by Example 1 and Example 2, it can be found that as the Al ion concentration increases, the emission intensity increases.
[0055] As Figure 5 shown is the fluorescence lifetime spectra corresponding to the emission peaks at 1.5 μm and 2.3 μm of the prepared Tm 0.005 Al 0.3 Ca 0.695 F2 samples under 808 nm light excitation. It can be seen that the lifetime of the 3 H4 energy level of the sample is 1.36 ms, 3 and the lifetime of the
[0056] Comparative Example 1
[0057] A thulium-doped calcium fluoride near mid-infrared band laser crystal Tm 0.005 Ca 0.995 F2, the preparation method thereof is the same as that of Example 1.
[0058] As Figure 6 shown is the room temperature fluorescence spectra of the prepared Tm 0.005 Ca 0.995 F2 samples at 1.5 μm and 2 μm. It can be seen that Tm 3+ does not split fluorescence peaks at around 1420 nm and 2050 nm.
[0059] As Figure 7 shown is the fluorescence lifetime spectra corresponding to the emission peaks at 1.5 μm and 2.3 μm of the prepared Tm 0.005 Ca 0.995 F2 samples under 808 nm light excitation. It can be seen that the lifetime of the 3 H4 energy level of the sample is 1.05 ms, 3 and the lifetime of the
[0060] The above description of the embodiments is provided to enable those of ordinary skill in the art to understand and use the invention. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative efforts. Therefore, the present invention is not limited to the above embodiments, and all improvements and modifications made by those skilled in the art without departing from the scope of the present invention according to the disclosure of the present invention should be within the protection scope of the present invention.
Claims
1. A thulium and aluminum co-doped calcium fluoride near-infrared laser crystal, characterized in that, The chemical composition of the laser crystal is expressed as Tm x Al y Ca 1-x-y F2, where 0.001 ≤ x ≤ 0.01 and 0.05 ≤ y ≤ 0.
5.
2. A thulium-aluminum co-doped calcium fluoride near-infrared laser crystal according to claim 1, characterized in that, x = 0.005, 0.1 ≤ y ≤ 0.
5.
3. The thulium-aluminum co-doped calcium fluoride near-infrared laser crystal according to claim 2, wherein, The space group of the described crystal is Fm-3m, belonging to the cubic crystal system.
4. A method for preparing a thulium-aluminum co-doped calcium fluoride near-infrared band laser crystal according to any one of claims 1 to 3, characterized in that, It includes the following steps: 1) Using TmF3, AlF3, and CaF2 as raw materials, calculate the required mass of each raw material according to the chemical formula Tm x Al y Ca 1-x-y F2, and weigh them; grind thoroughly and mix evenly. Weigh the deoxidizer and mix it with the raw materials to obtain a mixed material; 2) Place the mixed materials in step 1) in a protective gas; then process them through a procedure of heating - heat preservation - slow cooling - cooling to obtain a thulium-aluminum co-doped calcium fluoride near-infrared band laser crystal.
5. The preparation method of the thulium-aluminum co-doped calcium fluoride near-infrared band laser crystal according to claim 4, wherein The grinding time in step 1) is 40 - 60 min.
6. The preparation method of thulium-aluminum co-doped calcium fluoride near-infrared laser crystal according to claim 4, characterized in that, The deoxidizer in step 1) is PbF2; the addition amount of the deoxidizer is 1 - 3% of the total mass of TmF3, AlF3, and CaF2.
7. The preparation method of the thulium-aluminum co-doped calcium fluoride near-infrared band laser crystal according to claim 4, characterized in that, The protective gas in step 2) is at least any one of argon or fluorine-containing gas; the fluorine-containing gas is at least any one of CF4 or HF.
8. The preparation method of the thulium-aluminum co-doped calcium fluoride near-infrared band laser crystal according to claim 4, characterized in that The heating in step 2) is: heating to 1400 - 1700 °C at a rate of 200 - 300 °C / h; the heat preservation time is 10 - 15 hours.
9. The preparation method of the thulium-aluminum co-doped calcium fluoride near-infrared laser crystal according to claim 4, characterized in that, The slow cooling is: slowly cooling to 1000 - 1200 °C at a rate of 1 - 3 °C / h for crystal growth; the cooling is: after the slow cooling crystal growth is completed, cooling to room temperature at a rate of 50 - 60 °C / h.
10. Application of a thulium-aluminum co-doped calcium fluoride near-infrared laser crystal as described in any one of claims 1 to 3, characterized in that, The laser crystal is used as a gain medium to construct a high-power near-infrared band laser.
Citation Information
Patent Citations
Thulium-fluorine-yttrium-calcium-doped composite near-middle infrared band laser crystal and preparation method thereof
CN115864119A
Three-wavelength intermediate infrared solid laser based on Tm < 3 + > doped crystal and working method
CN117458254A